"Slowly But Sure": A Language Deficit of a Child with Down Syndrome - Rahmah, Aisyah Tiara; Sudarwati, Emy (Indonesian Journal of Disability Studies, 2021)
This is a case study research in this paper reports on findings from the case study (syntactic and morphological) in an individual diagnosed with a genetic disorder, Down Syndrome (DS), that affect language development without getting the help of any official therapists. We perform pragmatic and phonological analyses alongside morphology and syntactic analyses on data collected from studying documents, observation, and interview results. The qualitative descriptive linguistic method is used in this study to provide a detailed description. The result shows some deficits performed by the DS caused by articulatory limitation, difficulty to follow some words in long statements, and difficulty to respond to the topic that he has not known before.